Jurisprudens moden - Chand, Hari (Petaling Jaya, Selangor: International Law Book Services, 2014)
Theory and historical development of jurisprudence.
In Malay.
Includes bibliographical references.
Puan Shaizimah Badzri/ Pemilihan Buku di PBAKL2024/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216390/ OC/ Innowawasan
Keywords: Jurisprudence; Jurisprudence -- History